2010
DOI: 10.1089/lap.2010.0218
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Nissen Fundoplication Versus Thal Fundoplication in Children: Comparison of Short-Term Outcomes

Abstract: There was no statistical difference in the short-term outcomes between laparoscopic Nissen and Thal fundoplication, apart from a higher rate of esophagoscopy for severe dysphagia in the Nissen group. The higher number of postoperative complications in the Nissen group was largely due to gastrostomy-related problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
(35 reference statements)
2
14
1
Order By: Relevance
“…Only two RCTs were identified, and only five articles used control groups to verify their results 6,810,14,23. Most studies used standardized surgical methods and investigation techniques and reported adequate on lost to follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Only two RCTs were identified, and only five articles used control groups to verify their results 6,810,14,23. Most studies used standardized surgical methods and investigation techniques and reported adequate on lost to follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5] However, there is little information on the long-term treatment outcomes of hiatal hernia in children. There are two main laparoscopic antireflux fundoplications that are currently performed: the "total wrap" technique, such as a Nissen fundoplication and the modified Nissen-Rossetti fundoplication, and the "partial wrap" technique, such as the Thal fundoplication and the Toupet fundoplication.…”
Section: Introductionmentioning
confidence: 99%
“…Kubiak et al [17] reported dysphagia rates of 13.5% and 11.6% for each respective fundoplication, but the rates of severe dysphagia for Nissen and Thal were 10.1% and 1.7%, respectively (P = 0.018) in that study. In our current study, we experienced only one dysphagia cases among the HH patients.…”
Section: Discussionmentioning
confidence: 71%
“…Nissen fundoplication is the most widely performed but is associated with a high incidence of postoperative dysphagia and an appreciable recurrence rate in children with disabilities [13,14,15,16]. Thal is a partial wrap and is also widely performed, and is reported to be a simple and safe operative treatment in children with fewer perioperative complications and better long-term outcomes [17,18]. Surgical outcomes of both Thal and Nissen fundoplications as additional antireflux procedures for HH were good among our current study patients and there was no recurrence of HH in this series.…”
Section: Discussionmentioning
confidence: 99%